Race a philosophical introduction - Taylor, Paul C. 1967- (Polity Press, 2022)
The language of race -- Unnatural histories -- Three challenges to race-thinking -- What races are: twenty questions about racial metaphysics -- Ethics, existence, experience -- The color question -- A funny thing happened on the way to post-racialism
Includes bibliographical references and index
Keywords: Rasse; Philosophie; Race / Philosophy; Race relations / Philosophy; Einführung